A novel CFFOPI-FOPID controller for AGC performance enhancement of single and multi-area electric power systems. (May 2020) - Arya, Yogendra
Abstract: The modern power system (PS) is an intricate manmade control system. Automatic generation control (AGC) executes an imperative contribution in PS operation to preserve its frequency and tieline power flow within a tolerable range following continuously varying load demands. Hence, a wholesome and expert controller for AGC is obligatory to deliver superior power to the end users. The objective of this article is to design a cascaded fuzzy fractional order (FO) PI-FOPID (CFFOPI–FOPID) controller as a novel control strategy for AGC problem solution in electric PS. The controller parameters are determined employing a recent stochastic imperialist competitive algorithm. The controller assures the convergence of deviation in area frequency and tieline power under load disturbances to zero in minimum definite time. Single and interconnected multi-area thermal PS models are utilized as test systems to authorize the efficacy of the method. Results analysis reveals the advantage of CFFOPI–FOPID​ controller over various prevalent controllers. The models are also explored with appropriate generation rate constraint. Robustness test validates controller's robustness at large changes in system parameters, random change in power demand and additional imperative nonlinearities. Highlights: A new CFFOPI–FOPID controller is presented for AGC of power systems. Optimal parameters of the controller are acquired adopting ICA. Isolated and interconnected power systems are simulated to show the effectiveness of the controller. The supremacy of the controller in established over various existing controllers. Robustness of the controller is verified via robustness analysis.